Impact of Copper-Doped Mesoporous Bioactive Glass Nanospheres on the Polymerisation Kinetics and Shrinkage Stress of Dental Resin Composites - Marovic, Danijela; Par, Matej; Taubock, Tobias T.; Haugen, Havard J.; Mandic, Visnja Negovetic; Wuethrich, Damian; Burrer, Phoebe; Zheng, Kai; Attin, Thomas; Tarle, Zrinka; Boccaccini, Aldo R. (International Journal of Molecular Sciences, 2022)
We embedded copper-doped mesoporous bioactive glass nanospheres (Cu-MBGN) with antibacterial and ion-releasing properties into experimental dental composites and investigated the effect of Cu-MBGN on the polymerisation properties. We prepared seven composites with a BisGMA/TEGDMA (60/40) matrix and 65 wt.% total filler content, added Cu-MBGN or a combination of Cu-MBGN and silanised silica to the silanised barium glass base, and examined nine parameters: light transmittance, degree of conversion (DC), maximum polymerisation rate (R-max), time to reach R-max, linear shrinkage, shrinkage stress (PSS), maximum PSS rate, time to reach maximum PSS rate, and depth of cure. Cu-MBGN without silica accelerated polymerisation, reduced light transmission, and had the highest DC (58.8 +/- 0.9%) and R-max (9.8 +/- 0.2%/s), but lower shrinkage (3 +/- 0.05%) and similar PSS (0.89 +/- 0.07 MPa) versus the inert reference (0.83 +/- 0.13 MPa). Combined Cu-MBGN and silica slowed the R-max and achieved a similar DC but resulted in higher shrinkage. However, using a combined 5 wt.% Cu-MBGN and silica, the PSS resembled that of the inert reference. The synergistic action of 5 wt.% Cu-MBGN and silanised silica in combination with silanised barium glass resulted in a material with the highest likelihood for dental applications in future.
CRIS-Team WoS Importer:2022-08-26